Disruption of Maternal Parenting Circuitry by Addictive Process: Rewiring of Reward and Stress Systems - Rutherford, Helena; Williams, Sarah; Moy, Sheryl; Mayes, Linda; Johns, Josephine (Frontiers in Psychiatry, 2011)
Addiction represents a complex interaction between the reward and stress neural circuits, with increasing drug use reflecting a shift from positive reinforcement to negative reinforcement mechanisms in sustaining drug dependence. Preclinical studies have indicated the involvement of regions within the extended amygdala as subserving this transition, especially under stressful conditions. In the addictive situation, the reward system serves to maintain habitual behaviors that are associated with the relief of negative affect, at the cost of attenuating the salience of other rewards. Therefore, addiction reflects the dysregulation between core reward systems, including the prefrontal cortex (PFC), ventral tegmental area (VTA), and nucleus accumbens (NAc), as well as the hypothalamic-pituitary-adrenal axis and extended amygdala of the stress system. Here, we consider the consequences of changes in neural function during or following addiction on parenting, an inherently rewarding process that may be disrupted by addiction. Specifically, we outline the preclinical and human studies that support the dysregulation of reward and stress systems by addiction and the contribution of these systems to parenting. Increasing evidence suggests an important role for the hypothalamus, PFC, VTA, and NAc in parenting, with these same regions being those dysregulated in addiction. Moreover, in addicted adults, we propose that parenting cues trigger stress reactivity rather than reward salience, and this may heighten negative affect states, eliciting both addictive behaviors and the potential for parental neglect and abuse.